Lipid II-independent trans Editing of Mischarged tRNAs by the Penicillin Resistance Factor MurM - Shepherd, Jennifer (American Society for Biochemistry and Molecular Biology, 2013)
Streptococcus pneumoniae is a causative agent of nosocomial infections such as pneumonia, meningitis, and septicemia. Penicillin resistance in S. pneumoniae depends in part upon MurM, an aminoacyl-tRNA ligase that attaches l-serine or l-alanine to the stem peptide lysine of Lipid II in cell wall peptidoglycan. To investigate the exact substrates the translation machinery provides MurM, quality control by alanyl-tRNA synthetase (AlaRS) was investigated. AlaRS mischarged serine and glycine to tRNA(Ala), as observed in other bacteria, and also transferred alanine, serine, and glycine to tRNA(Phe). S. pneumoniae tRNA(Phe) has an unusual U4:C69 mismatch in its acceptor stem that prevents editing by phenylalanyl-tRNA synthetase (PheRS), leading to the accumulation of misaminoacylated tRNAs that could serve as substrates for translation or for MurM. Although the peptidoglycan layer of S. pneumoniae tolerates a combination of both branched and linear muropeptides, deletion of MurM results in a reversion to penicillin sensitivity in strains that were previously resistant. However, because MurM is not required for cell viability, the reason for its functional conservation across all strains of S. pneumoniae has remained elusive. We now show that MurM can directly function in translation quality control by acting as a broad specificity lipid-independent trans editing factor that deacylates tRNA. This activity of MurM does not require the presence of its second substrate, Lipid II, and can functionally substitute for the activity of widely conserved editing domain homologues of AlaRS, termed AlaXPs proteins, which are themselves absent from S. pneumoniae.